MOTHERS' HYPERTENSION AND NEONATAL BIRTH WEIGHT - M. Madadzadeh; Z. Feizi; ES Hajikazemi; H. Haghani (Iran University of Medical Sciences, 2005)
Pregnancy induced hypertension has impacts on birth weight in different gestational ages, and deciding on preventive modalities is mainly based on comprehension of birth weight in different gestational ages. To approach this objective we performed a comparative retrospective study and compared the birth weight of neonates of mothers with and without pregnancy induced hypertension in different gestational ages with the participation of 250 hypertensive and 458 nonhypertensive mothers. Finding revealed significant differences between hypertension in pregnancy and birth weight in 36th and 37th weeks of gestation (P=0.15) and (P=0.019) respectively. The differences varied according the number of pregnancies, for instance, meanwhile, for nulliparas in 36th, 38th, 39th and 41st weeks, it was respectively, (P=0.008), (P=0.022), (0.033) and (P=0.49), in multiparas, with less that 5 pregnancies in 39th week the P value was (0.49), but in women with 5 and/or more pregnancies there was not any significant differences.  According to the findings pregnancy-induced hypertension will results in fetal low weight in different weeks of gestation. So, the researchers recommend useful services to be provided in different weeks of pregnancy.